Χωρική κατανομή, εποχικότητα και τύποι αερολυμάτων από LIVAS στη λεκάνη της Μεσογείου - Καπλάνη, Αγγελική-Μαρία (2016)
The energy balance between the atmosphere and planet Earth directly affects the climate. Both greenhouse gases and particulate matter are important factors in changing the energy balance and, hence, climate change. The presence of aerosols causes warming or cooling of the Earth and affects, directly and indirectly, the climate’s character through absorption, retransmission and scattering of radiation coming from the sun. It is important to study the vertical distribution of aerosols in the atmosphere in order to understand the aerosols’ impact on the energy balance. One of the main parameters to look at in order to describe aerosols, is the aerosol optical depth (AOD). With this piece of research, an attempt was made to calculate the AOD per height of the atmosphere in the Mediterranean basin during the period of 01/01/2008 - 31/12/2011. Values sourced from the European Space Agency aerosol LIVAS database were used for calculating results and extracting maps and corresponding diagrams. Aerosol Extinction Mean illustrations – maps, seasonality and types of particulate matter are presented in this thesis. Furthermore, diagrams of the distributions of the aerosol optical depth are presented, in relation to heights of the atmosphere, for better visualization and understanding. Processing the available data, a first conclusion is that larger aerosol optical depths are found in the lower layers of the troposphere, up to 2 km. The areas where this occurs to a greater extent are the coast of North Africa, particularly Morocco, Syria, the Balkan Peninsula and, occasionally, areas of northern Italy. Summer and Spring are the seasons with higher AOD in the 0.5 km height, unlike Autumn and Winter which are characterized by lower AOD. Finally, the highest share in the total aerosols throughout the atmosphere in the Mediterranean basin is held by the Polluted Dust and the AOD with the highest observed value belongs to Polluted Continental, which is located in a specific area in the northwest coast of Africa.